Inovasi program penguatan pendidikan karakter religius berbasis profil pelajar Pancasila di SMP Al-Kahfi - Syafri, Ulil Amri; Bawazier, Farhad Ali; Tamam, Abas Mansur; Mujahidin, Endin (Ta'dibuna: Jurnal Pendidikan Islam, 2022)
The Independent Curriculum Policy launched by the Minister of Education and Culture of the Republic of Indonesia is to produce an output of Pancasila student profiles. This study was carried out to determine how Islamic educational institutions, in this case, secondary schools, can produce Pancasila student profiles through school-based programs. The aim is to describe innovations in programs to strengthen religious character education based on Pancasila student profiles at Al-Kahfi Middle School, Bogor. The subjects in this study were students at SMPIT Al-Kahfi, Bogor. Data was collected through interviews, observation, and documents. The results of this study indicate that the achievement of educational profile competencies is carried out through strengthening religious character education (faith, piety to God Almighty, and having a noble character) at SMPIT Al-Kahfi with its distinctive method. Supporting and inhibiting factors in strengthening religious character education programs were also found. Abstrak Kebijakan Kurikulum Merdeka yang dicanangkan Menteri Pendidikan dan Kebudayaan RI adalah melahirkan output profil pelajar Pancasila. Penelitian ini dilakukan untuk melihat bagaimana lembaga pendidikan Islam, dalam hal ini sekolah tingkat menengah, dapat melahirkan profil pelajar Pancasila melalui program di sekolah. Tujuannya adalah untuk mendeskripsikan inovasi-inovasi program penguatan pendidikan karakter religius berbasis profil pelajar Pancasila di SMP Al-Kahfi, Bogor. Subyek dalam penelitian ini adalah siswa dan siswi SMPIT Al-Kahfi, Bogor. Data dikumpulkan melalui wawancara, observasi dan dokumen. Hasil penelitian ini menunjukkan bahwa pencapaian kompetensi profil pendidikan dilakukan melalui penguatan pendidikan karakter religius (beriman, bertakwa kepada Tuhan YME, dan berakhlak mulia) di SMPIT Al-Kahfi dengan metodenya yang khas. Faktor pendukung dan penghambat dalam program penguatan pendidikan karakter religius juga ditemukan.